Energy-dependent machining mechanism and process in water-jet guided laser processing single crystal diamond - Shilong Chen; Tianye Jin; Zihao Lin; Mingtao Wu; Junquan Huang; Junyun Chen; Anmin Nie (Alexandria Engineering Journal)
Water-Jet Guided Laser (WJGL) machining is an outstanding technique for efficiently and flexibly machining single crystal diamond components. However, the machining mechanism and process are still indistinct. In this work, critical laser condition for material removal was proposed. Critical laser fluence dynamically changed from 48.3 J/cm2 to 77.5 J/cm2 for laser power of 8 W to 20 W. Subsequently, ablation mechanism was discussed in view of the microscopic morphology and surface characterization. The diamond material was incompletely softened and transited to sp2-dominated amorphous composition with partial diamond polycrystallization under low energy, when the laser power was ≤ 14 W. To the contrary, material was sufficiently softened under high energy and removed by water washing, resulting in a finished surface featuring micro breakage and sp3-dominated amorphous subsurface. At last, energy-dependent influence on machining outcomes was investigated. High-energy ablation (laser power of ≥16 W) was beneficial to promote kerf straightness, aspect ratio, material removal rate (MRR) and surface quality, owing to high-energy ablation mechanism for complete and clean material removal. Micro groove with parallel side wall and high aspect ratio (maximum of 16.7) was fabricated. The MRR reached up to 17.3 × 10−3 mm3/s, and smooth surface with roughness of Sa< 200 nm was achieved.